The indigenous sheep of Nigeria - Adu, I.F.; Ngere, L.O. (1979)
There are four main breeds of sheep in Nigeria. The breeds are Balami, Uda, west African Dwarf sheep and Yankasa. Balami is most predominant in the North eastern part of Nigeria. The Balami is a predominantly white and hairy breed with a pronounced convex heat and a dull depression. It has a dewlap-like fold of skin with white mane. The ear is large and droopy. The tail is long. Horns are prominent in rams and are usually absent in ewes. The Balami is fast growing and attains a weaning weight of 18 kg in 12 weeks. The yearling weight is 35 – 40kg for ewes and 45 – 60kg for rams. Uda breed occurs throughout the Sahelo-sudan vegetation zone of Nigeria. It is a large and long-lopped breed with a convex facial profile. The coat colour is entirely brown or black from the forehead anterior to the limber-abdominal girth line and white posterior. The ears are long large and pendulous. The rams have large wide and spiral horns, which are usually absent in the ewes. The breed appears to thrive in hot, dry environment and suffers from poor survival outside this ecological zone; it is particularly adapted to extensive grazing and is renowned for its trekking abilities. Mature weights range from 35 - 45kg for ewes and 45 – 55kg for rams. The Yankasa breed is widely distributed in the northern part of Nigeria. In size it is intermediate between Uda and the west African Dwarf sheep. The coat colour of Yankasa is typically white with black patches around the eyes, ear, muzzle and sometimes the feet. The rams have curved horns and heavy hairy white mane. Some of the ewes have tassels on the neck. Mature weights are 25 – 40 kg for ewes and 35 – 50 kg for rams. The west African dwarf sheep is widely distributed in the southern Nigeria, the breed is small compact hardy breed with a wide range of coat-colour which may be all white, black or brown or spotted black or brown on a white coat. The breed is considered to be tolerant to trypanosomiasis. Mature weights are 20 – 25kg for ewes and 25 – 30 kg for rams.